Studies on the cyclone dipleg flow characteristics in a CFB for designing 3 MWth scale chemical looping combustor. (15th August 2022) - Kim, Daewook; Jang, Jae Jun; Nam, Hyungseok; Kim, Jae Young; Won, Yooseob; Lee, Seung-Yong; Hwang, Byung Wook; Choi, Yujin; Kim, Hana; Baek, Jeom-In; Ryu, Ho-Jung
Abstract: 3 MWth scale chemical looping combustion (CLC) system using circulating fluidized bed (CFB) is being developed as a liquidized natural gas power generation technology to reduce CO2 emissions. Dipleg, considered a blood vessel of CFB, conveys solids captured by cyclone to the fluidized bed while preventing gas mixing. This vertical passage plays key role in solids circulation and cyclone performance in thousands of CFB systems, yet only a limited information is available on its design and operation. This study experimentally investigated the flow characteristics in dipleg to verify design and operating conditions for smooth solid flow while predicting the amount of gas mixing. When solid circulation rate increased, both upward and downward gas flowrates in dipleg increased. It was found that the sum of two flowrates were equal to the volumetric flowrate of solids in the dipleg. Unstable operation occurred when 1) the gas-solid relative velocity in the dipleg became higher than the minimum slugging velocity, and 2) bubble diameter in bubbling bed became larger than the dipleg diameter. Finally, models for operation range and the amount of gas mixing in dipleg were proposed, and the design and operation range of the dipleg in 3 MWth scale CLC was suggested. Graphical abstract: Gas flows and design range of a dipleg in 3 MWth chemical looping combustor derived in this study. Image 1 Highlights: Applicability of dipleg in CFB was investigated and design factors were confirmed. The amount of up- and down-stream gas was measured within dipleg. Almost same amount of gas was exchanged with the down-stream particles. Slugging in dipleg interfered the solid flow. Bubble, larger than dipleg diameter, prevents the solid flow within dipleg.